Temperature distributions of internal flow and external jet fields of double serpentine convergent nozzle for turbofan - Sun Peng; Zhou Li; Wang Zhanxue; Shi Jingwei (Xibei Gongye Daxue Xuebao, 2021)
In order to clarify the temperature distribution of a double-serpentine convergent nozzle wall and the exhaust plume characteristics downstream the nozzle exit based on the real exhaust mixer configuration of a turbofan engine, the temperature distribution of the internal and external jet flow fields of the double-serpentine convergent nozzle are simulated numerically. The simulation results show that the coupling effect between S-shaped circular-to-rectangular profile and the exhaust mixer has a joint influence on the "hot streak" distribution of the double-serpentine convergent nozzle wall and the exhaust plume characteristics downstream the nozzle exit. The "Hot streak" is distributed in the shape similar to several ribbons in the central areas of the upper and lower wall of the second serpentine passage and in the exit area. The maximum value of temperature on the lower wall is 867 K and increases 25.1% compared with that on the upper wall. However, the average value of temperature of the lower wall is merely 7.1% higher than that of the upper wall. The "whale tail" high-temperature core area is formed on the exit plane of the double-serpentine convergent nozzle. It leads to two wide high-temperature jet flow areas in the high-temperature core area downstream the nozzle exit. The low-temperature flow occurs along the two sides of the exhaust plume core area due to the lateral-direction motion towards vortices.